Legal Framework for Human Rights Protection in Americas - Tabaszewski, Robert (Regional Human Rights Protection Systems Outside Europe, 2026)
This study presents the development of the legal framework for human rights protection in the Americas. It addresses the historical context of continental integration. Key to this foundation were the Pan-American Congresses and the establishment of the International Union of American Republics at the turn of the 19th and 20th centuries, initiating a framework for human rights protection in the region. The institutionalisation of protective mechanisms for individual rights is traced back to 1948, marking a pivotal development for the OAS. The analysis focuses on key legal instruments, such as Bogotá Charter, American Declaration of the Rights and Duties of Man and American Convention on Human Rights, along with additional Protocols and a set of specialised conventions, including the Inter-American Convention to Prevent and Punish Torture, the Inter-American Convention on Forced Disappearance of Persons and the Inter-American Convention on the Prevention, Punishment and Eradication of Violence against Women and others. This study offers insights into how the OAS integrates new sets of norms and judicial mechanisms, such as the Inter-American Court, to meet contemporary human rights challenges across the continent. It also briefly considers how recent post-pandemic legal and institutional developments have influenced the evolution of human rights protection in the Americas. Keywords: Inter-American System, Inter-American Court, Human Rights Law, American Convention, Legal Instruments, Human Rights Treaties